Transformation of Digitaria sanguinalis with XvPer1, a novel antioxidant - Chigorimbo-Tsikiwa, Nyaradzo T L (Department of Molecular and Cell Biology, 2023)
Digitaria sanguinalis, a widespread African grass, was micropropagated from immature inflorescences. Embryogenic calli generated was transformed with XvPerl using the Biolistic gene gun. XvPer 1 shares high similarity to a recently discovered group of antioxidants, the 1-Cys PRX's. A homologue was shown to be absent in D. sanguinalis by northern, Southern and weotstern Bls.